Employee Engagement, Leadership Style, and Work Motivation on Employee Performance - Inganatul Khasanah; Teguh Setiawan Wibowo; Murthada; Noorhani Dyani Laksmi (Malaqbi Publisher, 2026)
This study aims to examine the influence of employee engagement, leadership style, and work motivation on employee performance. A quantitative research approach was employed using a cross-sectional survey design. Data were collected from 200 employees through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using descriptive statistics, validity and reliability tests, and multiple linear regression analysis. The results indicate that employee engagement, leadership style, and work motivation have positive and significant effects on employee performance, both partially and simultaneously. Among the independent variables, leadership style was found to have the most dominant influence on employee performance, followed by work motivation and employee engagement. The coefficient of determination (R²) shows that 55.5% of the variance in employee performance can be explained by the three variables, while the remaining 44.5% is influenced by other factors not examined in this study. These findings highlight the importance of effective leadership, high employee engagement, and strong motivation in enhancing employee performance. The study provides practical implications for organizations to develop integrated human resource strategies that focus on leadership development, employee involvement, and motivational systems to achieve optimal organizational outcomes.